2012
DOI: 10.1159/000343249
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Fine-Needle Aspiration of Thyroid Nodules Measuring Less than 5 mm: Effects on Specimen Adequacy and Diagnosis

Abstract: Objective: We aimed to assess the adequacy and efficacy of ultrasound (US)-guided fine-needle aspiration (US-FNA) for small solid thyroid nodules (SSTNs) with the largest diameter <5 mm and compared these according to nodule size. Study Design: Among 656 SSTNs in 569 patients, each SSTN was classified into 1 of 4 groups according to the largest diameter: 1 mm ≤ group A < 2 mm; 2 mm ≤ group B < 3 mm; 3 mm ≤ group C < 4 mm, and 4 mm ≤ group D < 5 mm. We compared the adequacy and efficacy of US-FNA between these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…Compared to prior studies, our total sensitivity and PPV were in the upper range, and the total specificity and NPV were in the lower range because of the small percentage of benign nodules in this pathologically based study. Previous studies reported 1.4% to 10.5% false‐negative rates and 1.9% to 31% false‐positive rates for US‐guided FNA comparing cytologic and corresponding histopathologic results . The total false‐negative and false‐positive rates in this study were 4.7% and 16.7%, respectively.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Compared to prior studies, our total sensitivity and PPV were in the upper range, and the total specificity and NPV were in the lower range because of the small percentage of benign nodules in this pathologically based study. Previous studies reported 1.4% to 10.5% false‐negative rates and 1.9% to 31% false‐positive rates for US‐guided FNA comparing cytologic and corresponding histopathologic results . The total false‐negative and false‐positive rates in this study were 4.7% and 16.7%, respectively.…”
Section: Discussioncontrasting
confidence: 39%
“…Bethesda I FNA results are the main drawback of the FNA technique. Kim et al reported that for 200 resected nodules smaller than 5 mm in diameter, the cytologic results tended to be nondiagnostic in tumors with small sizes. We agree with this conclusion, as tiny nodules have lower tissue volumes for aspiration (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the size of the smallest nodule that can be assessed with FNA is unclear. Some authors believe that the accuracy of FNA is reduced in nodules <6 mm [19], whereas other authors have shown that the diagnostic efficacy of FNA is lower for nodules with a maximum diameter of <3 mm [20]. The American Thyroid Association does not recommended routine FNA for nodules <5 mm because highly inadequate cytology specimens are produced [21].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, FNA has limitations in subcentimeter nodules as a result of its high rates of inadequate cytological specimens and false positive findings, especially for nodules less than 5 mm 4 . Therefore, it is essential to find new methods to improve the accuracy of PTMC diagnosis.…”
Section: Introductionmentioning
confidence: 99%